TV advertising and dietary intake in adolescents: a pre- and post- study of Chile's Food Marketing Policy - Melissa L. Jensen; Francesca R. Dillman Carpentier; Linda Adair; Camila Corvalán; Barry M. Popkin; Lindsey Smith Taillie (BMC, 2021)
Abstract Background The first phase of a comprehensive marketing policy was implemented in Chile in 2016. The policy restricted child-directed marketing of foods and beverages considered high in energy, total sugars, sodium or saturated fat ("high-in"). The objective of this study was to examine the role of high-in TV food advertising as a mediator in the association between policy implementation and consumption of high-in foods and beverages between 2016 and 2017. Methods Dietary data were from 24-hour diet recalls collected in 2016 and 2017 in a cohort of 12-14 y children (n = 721). Television use was assessed concurrently and linked to analyses of food advertisements on broadcast and paid television to derive individual-level estimates of exposure to high-in food advertising. A multilevel mediation analysis examined direct and indirect effects of the policy through advertising exposure. Results Following the policy implementation, high-in advertising exposure was significantly reduced (p < 0.01). High-in food intake decreased in adolescents with lower levels, but not higher levels, of high-in advertising at baseline. We did not find evidence of mediation by changes in high-in ad exposure. Conclusions Adolescents' exposure to high-in TV advertising decreased after the 2016 implementation of the Chilean Food Labeling and Marketing Law. However, evidence that changes in advertisement mediated dietary changes was not found. Further research is needed to understand how marketing changes will relate to dietary changes after full implementation of the law and in the long term.